PEPDar: A randomized prospective noninferiority study of ritonavir‐boosted darunavir for HIV post‐exposure prophylaxis. Issue 6 (11th May 2016) - Fätkenheuer, G; Jessen, H; Stoehr, A; Jung, N; Jessen, AB; Kümmerle, T; Berger, M; Bogner, JR; Spinner, CD; Stephan, C; Degen, O; Vogelmann, R; et al.
Abstract : Objectives: PEPDar compared the tolerability and safety of ritonavir‐boosted darunavir (DRV/r)‐based post‐exposure prophylaxis (PEP) with the tolerability and safety of standard of care (SOC). The primary endpoint was the early discontinuation rate among the per‐protocol population. Methods: PEPDar was an open‐label, randomized, multicentre, prospective, noninferiority safety study. Subjects were stratified by type of event (occupational vs . nonoccupational, i.e. sexual) and were randomized to receive DRV/r plus two nucleoside reverse transcriptase inhibitors (NRTIs) or SOC PEP. Twenty‐two private or university HIV clinics in Germany participated. Subjects were ≥ 18 years old and had documented or potential HIV exposure and indication for HIV PEP. They initiated PEP not later than 72 h after the event and were HIV negative. Results: A total of 324 subjects were screened, the per‐protocol population was 305, and 273 subjects completed the study. One hundred and fifty‐five subjects received DRV/r‐based PEP and 150 subjects received ritonavir‐boosted lopinavir (LPV/r)‐based PEP for 28–30 days; 298 subjects also received tenofovir/emtricitabine. The early discontinuation rate in the DRV/r arm was 6.5% compared with 10.0% in the SOC arm ( P = 0.243). Adverse drug reactions (ADRs) were reported in 68% of DRV/r subjects and 75% of SOC subjects ( P = 0.169). Fewer DRV/r subjects (16.1%) had at least one grade 2 or 3 ADR compared with SOC subjects (29.3%) ( P = 0.006). All grades of diarrhoea, nausea, and sleep disorders were significantly less frequent with DRV/r, while headache was significantly more frequent. No HIV seroconversion was reported during follow‐up. Conclusions: Noninferiority of DRV/r to SOC was demonstrated. DRV/r should be included as a standard component of recommended regimens in PEP guidelines.